From Volatility to Stability in Expenditure : Stabilization Funds in Resource-Rich Countries - Sugawara, Naotaka (IMF Working Papers; Working Paper, 2014)
This paper examines the effect of stabilization funds on the volatility of government expenditure in resource-rich countries. Using a panel data set of 68 resource-rich countries over 1988-2012, the results find that the existence of stabilization funds contributes to smoothing government expenditure. The spending volatility in countries that have established such funds is found to be 13 percent lower in the main estimation, and similar impacts are found in robustness tests. The analysis also shows that political institutions and fiscal rules are significant factors in reducing the expenditure volatility, while highlighting the roles of the size of economy, diversified exports, real sector management, and financial markets.